Comparative Analysis of a Dollarization Process in Argentina in Relation to the Process in Ecuador. - Dávila Toro, Luis Alberto (2024)
This research has been focused on analyzing the causes that produced the dollarization process in Ecuador, in order to identify the behavior of certain economic and social variables through their historical study from that moment, determining the causes that led to this decision, and the results that they have produced in the short and medium term. Subsequently, through the study of the timeline of the same variables but in Argentina, conclude the effects that could be produced in the hypothetical case that this last country also dollarizes. This study does not intend to justify that dollarizing is beneficial or not, but to compare the similarities and differences between two countries